Attitude of Undergraduate Students towards Gamification: A Case Study of Northwest Geo-Political Zone, Nigeria - Auwalu Rabiu Ali; Azizah Endut; Rahimah Embong (Pejabat Karang Mengarang UPSI, 2018)
Gamification of education is new field in education that is attracting researchers who are passionate on education. However, no much researches were made to assess the users' perception on its application in enhancing students understanding of certain subjects such as Environmental Education. This article is aimed at assessing the students' attitude on the application of eeGamification in environmental education. The method employed was survey method. A structured questionnaire was used and a total of 372 respondents were used in the study. The survey employed descriptive statistics analysis to measure the level of students' attitude towards eeGamification. The result indicates that students have positive attitude towards gamification. This shows that students accept the idea of gamification in improving students' understanding of Environmental Education.